Propuesta de aprovechamiento de alimentos agrícolas en la ciudad de Bogotá: Una mirada a la logística de distribución (2021)
The Bogotá city has evidenced an increase in waste related with the agricultural food as a consequence of the different factors associated with the improper handling that has occurred in the commercialization and distribution phases; focusing mainly in the small and medium marketplaces known as “fruvers”, this project proposes the creation of a proposition that favors society and the environment of the city, at the same time that contributes at fulfillment of the ODS - Objetivos de Desarrollo Sostenible, with the application of initiatives that positively influence.